EFL Learners’ Experiences in Using Zoom Meeting during COVID-19 Outbreak - Dewi Atikah; Nurwijayanti Nurwijayanti (AL LUGHAWIYAAT, 2022)
Because of Covid-19 pandemic, the use of online platform, included Zoom meeting, in EFL classroom facilitating the learning process is gaining ground. As the students are widely involved in the use of this platform, it is essential to investigate the students’ experience in using the platform. Using questionnaire and reflection, the data were collected from seventeen English Education Department students, and analyzed qualitatively based on the intrinsic pleasantness, novelty, goal/need significance, coping potential, and norm/self-compatibility. The study indicates that the students experienced the benefits of the platform in learning such as it can help them to learn and resemble the real class, its various interesting features enables us to record and save videos during the meeting, to use the filter, to schedule online meetings, to facilitate clear presentations like displaying power points, to use a video call. However, most of the students sometimes need to cope with the unstable network which is one of the requirements to use Zoom meeting. Therefore, this study implies that Zoom meeting can be a good alternative to change the teaching and learning process in real classroom during Covid-19 outbreak.  Keywords: COVID-19; Learners’ experience; Zoom platform.